The high biodiversity of benthic organisms in a coastal ecosystem revealed by an integrative approach - Cecília, A.; Amaral, Z.; Cunha, Beatriz P.; Checon, Helio H.; De Godoy, Angélica S.; Da Silva, Camila F.; Corte, Guilherme N.; De M. Nogueira, João M.; Fukuda, Marcelo V.; Steiner, Tatiana M.; Kawauchi, Gisele Y.; Turra, Alexander; et al. (FapUNIFESP (SciELO), 2024)
Increasing habitat modification and species loss demand consistent efforts to describe and understand biodiversity patterns. The BIOTA/FAPESP Program was created in this context and it has been a successful initiative to promote studies on biodiversity and conservation in Brazil. The BIOTA/Araçá is an interdisciplinary project that provided a detailed evaluation of the biodiversity of Araçá Bay, a coastal seascape located on the North coast of the state of São Paulo, Southeast Brazil. The bay encompasses multiple habitats, such as beaches, mangroves, rocky shores, and a tidal flat, and provides important ecosystem services. Unfortunately, the bay is the subject of complex social-environmental conflicts that oppose economic, social, and environmental demands (i.e., the expansion of neighboring harbor activities vs. small-scale artisanal fisheries and protection of biodiversity). The present study presents a survey of the benthic species occurring in the different habitats of Araçá Bay, including data obtained during the BIOTA/Araçá project and previous assessments of the area. The benthic species play an important role in marine environments and studying the diversity of these organisms that live associated with the bottom is indispensable for comprehending the environment’s functioning. The macrofauna, meiofauna, and microorganisms associated with soft and hard bottom were listed, and additional information, such as the habitat and geographical distribution, were provided for each species. The checklist includes 826 species, almost 70% recorded during the BIOTA/Araçá project. The most speciose taxa were the annelids (225 spp.), mollusks (194 spp.), and crustaceans (177 spp.). Seven benthic species are endemic to Araçá Bay, 14 are considered threatened, and seven are economically exploited. Furthermore, the bay is the type locality of many taxa, and 11 new benthic species were described based on specimens sampled during the project. This project shows the importance of Araçá Bay as a unique biologically rich environment and highlights the need for conservation efforts in light of the current threats.
A alta biodiversidade de organismos bentônicos em um ecossistema costeiro revelada por uma abordagem integrativa
Keywords: Araçá Bay; Checklist; Conservation; Macrofauna; Meiofauna; Microorganism